A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini) - Szawaryn, Karol; González, Guillermo (Zootaxa, 2017)
Although Gordon (1975) revised the herbivorous ladybirds of the New World, the taxonomy of this group in the Americas is still poorly studied. Some recent efforts have been made at the generic (Szawaryn 2015b) as well as species level (Szawaryn 2015a; González & Gómez 2013; González 2015) to describe and improve our knowledge of the systematics of Neotropical Epilachnini, but they still need more investigation.